Konsep Model Desain Pembelajaran pada Sekolah Dasar Islam Baiturahman di Kota Tangerang - Nurrahma, Maya Iga; Qodrawati, Romadona Yulia (Lembaga Yasin AlSys, 2022)
The concept most favored by students uses the practical method, because it is not as boring as the lecture method. Lower grade children prefer the learning method while playing. Learning is an activity designed by the teacher so that students carry out learning activities, to achieve the expected goals or competencies in designing this learning activity, a teacher should understand the characteristics of students, the learning objectives, to be achieved or the competencies that students must master, the teaching materials to be taught. presented, and the method used continues to package the presentation of the material as well as the use of the form and type of assessment that will be selected to measure the achievement of learning objectives or competencies that students have. With the concept of a practice model in Baiturrahman Islamic school, 80% of student learning objectives are achieved and student learning outcomes are good and good. When compared with other concepts, how about the concept of practical learning? the better the results of student scores after using the concept of practice the student's grades increased more than the other concepts.